A study on knowledge, attitude and practice regarding organ donation and transplantation among final year health science students in Bengaluru, Karnataka, India - S. G., Meghana; Subramanian, Mangala; Atmakuri, Sri Aditya; S., Tarun; Bera, Priyadarshini; J., Nelson (International Journal Of Community Medicine And Public Health, 2018)
Background: Organ transplantation is the most preferred modality for all end-stage organ diseases. Pre-requisites for the success of transplantation program include awareness, positive attitude of people towards the practice of organ donation. This study was carried out to assess the knowledge of organ donation among the final year medical, dental, nursing students and to study the attitude, religious beliefs of the health care professionals regarding organ donation and transplantation, to find out the effect of motivation, towards organ donation. Methods: A comparative, cross-Sectional study was conducted on 150 final year Medical, Dental and Nursing students of Vydehi Institute of Medical Sciences and Research Centre, Bengaluru over a period of 2 months. A questionnaire containing 3 sections of multiple choice questions was prepared and the knowledge, religious beliefs, attitude and practice on organ donation and transplantation was assessed. The data obtained was entered into SPSS Version 21.0. The qualitative variables were expressed as frequencies and percentages; quantitative variables as mean and standard deviation. Results: Out of the 150 participants, the mean knowledge score of Medical students was higher than that of Dental and Nursing students (p<0.01) and so was the mean belief score (p<0.05). The study motivated 34 (22.6%) students in total, who pledged their organs with the Zonal Co-ordination Committee of Karnataka. Conclusions: 33 (66%) of medical students who have significantly better knowledge have pledged their organs. This highlights importance of educating the society to bring a positive change in their thoughts, beliefs and practices towards organ donation and transplantation.